Aryne-Mediated Arylation of the 3-Benzazepine Scaffold: One-Pot Synthesis of 1-Aryl-3-methyl-2,3,4,5-tetrahydro-1H-3-benzazepines - Singh, Kamal Nain; Singh, Paramjit; Sharma, Esha; Kaur, Manjot; Deol, Yadwinder Singh (Synthesis, 2015)
The coupling of β-amino carbanions derived from 3-benzazepines with in situ generated arynes has been demonstrated as a convenient route for the direct synthesis of a variety of 1-aryl-3-methyl-2,3,4,5-tetrahydro-1H-3-benzazepines, including the biologically active drug molecule SCH 12679.
Keywords: arylation; arynes; carbanions; nucleophilic addition; drugs